CHILD HEALTH IN AFGHANISTAN: A GLIMPSE ON THE FUTURE OF A WAR STRICKEN COUNTRY - Khan, Mohammed Ibrahim; Khan, Samreen; Laaser, Ulrich; Chotani, Rashid (Journal of Ayub Medical College Abbottabad, 2003)
Afghanistan has one of the world’s poorest human development indicators1-3. Among the population of 24 million roughly 10.7 million are children under the age of 181,2. Figure-1 shows under five population in Afghanistan. Precise data showing country’s recent demographic and epidemiological profile is scarce as series of wars and political conflicts barely permitted such research intentions and health care interventions. The crisis of more than 23 years has left devastating effects on the health and well being of millions of children. It has killed over 1.5 million people, including more than 300,000 children2. An extensive review of contemporary literature is presented here to provide an account of social, physical, and mental health of Afghan children with an aim to depict the severity and complexity of the situation induced by war of more than a decade. Data on child vulnerability indicators were retrieved from MEDILINE, reports of WHO, and United Nations Agencies.